Rhizobacterial diversity, community composition, and the influence of keystone taxa on O’Neal blueberry (Vaccinium corymbosum) - Jia, Mingyun; Liu, Zhuangzhuang; Wei, Jiguang; Li, Qi; Hou, Zhaoqi; Sun, Ling; Yu, Hong; Yu, Jinping; Lu, Shipeng (Frontiers in Microbiology, 2024)
Rhizosphere microbiotas play vital roles in resisting environmental stress, transforming soil nutrients, and promoting plant health, growth, and productivity. The effects of rhizosphere microbial community shaping and the characteristics and functions of keystone taxa on blueberries were comprehensively studied by examining the rhizobacteria of healthy old trees (O), young seedlings (OG), and poorly growing seedlings (OB) of O'Neal blueberries. Our results showed that rhizobacterial diversity followed the order OB > > OG > O, and the microbial community of OG was similar to that of O, while that of OB was distinctly different. The predominant rhizobacteria identified included Actinobacteria, Proteobacteria, Firmicutes, Chloroflexi, and Acidobacteria. Firmicutes were highly enriched in healthy blueberries, with Bacillus identified as a key genus that significantly enhanced blueberry growth when inoculated. Bradyrhizobium and Gaiellales were common core bacteria in the blueberry rhizosphere. In contrast, Acidobacteria were the predominant phylum in poorly growing OB, with the specific Vicinamibacterales-related and Latescibacterota-related genera acting as keystone taxa that shaped the microbial community. In addition, bacterial species in Vicinamibacterales might act as a potential pathogen predicted by BugBase. Taken together, these findings provide fundamental insights into the development of the blueberry rhizosphere microbial community and highlight the role of beneficial rhizobacteria, such as Bacillus, in enhancing blueberry growth. This knowledge could contribute to the exploitation of beneficial rhizobacteria and the prevention of pathogens in modern agriculture.